Du crime à l’œuvre : la symbolique de la cage chez Kate Millett - Marie-Dominique Gil (Les Cahiers de l'École du Louvre)
Kate Millett is a major figure in American feminism. Known for her political commitment, she thought of herself primarily as a sculptor. Her work was deeply marked by an article she read about the murder of a young girl, a crime of unprecedented violence that, between 1967 and 1996, led her to utilise obsessively a certain object – the cage – in her sculpture. Her work created an organic link with the symbolic system fostered by this apparatus devoted to confinement. Exploring its possibilities in immersive installations in both performances and sculptures, she simultaneously deployed both her aesthetic and social potential. Her work reveals all the violence both generated and obscured by an erotic field rooted in a system of gendered signs.